Impact of boron fertilisation on soybean grain yield as affected by associated physiological factors - Freitas, Igor Libório; Teixeira, Gelza Carliane Marques [UNESP]; Campos, Cid Naudi Silva; Teodoro, Larissa Pereira Ribeiro; Rodrigues, Dágila Melo; Alvarez, Rita de Cássia Félix; Prado, Renato de Mello [UNESP]; Teodoro, Paulo Eduardo (Wiley, 2024)
High soybean yields generally requires fields to have an adequate supply of boron (B). However, there remains uncertainty around how different cultivars might respond to differing levels of available B. The objective of this study was to evaluate the effect of B fertilisation on physiological efficiencies, yield, and export of B in various soybean cultivars. A randomised block experiment was carried out under field conditions in Region, Brazil consisting of 10 soybean cultivars and two levels of B fertilisation (without application and with application of 3 kg ha−1 of B). Water-use efficiency, instantaneous carboxylation efficiency, B content in the seed, export of B, and grain yield were evaluated. There was a significant interaction between B fertilisation x genotypes for all variables evaluated. In general, B fertilisation improved physiological and nutritional characteristics, increasing grain yield and B seed content on average by 21% and 35%, respectively. The soybean cultivars 7110 and Soyoro showed increases in all physiological and agronomic variables evaluated with B fertilisation. The results of this research confirm that B fertilisation improves the physiological and agronomic performance of the majority of soybean genotypes evaluated.
Keywords: boron management; Glycine max (L.) merril; photosynthesis; plant physiology; water-use efficiency